Efektivitas Penggunaan Birthing Ball Dalam Mengurangi Nyeri Persalinan Kala I Fase Aktif - Jusmawati, Jusmawati; Sya'bin, Nurul; Hartinah, Asniah; Saputri, Resti Dona; Sriwahyuningsih, Ade; Asli, Kartika; Muldaniyah, Muldaniyah (Madu Jurnal Ilmu Kebidanan, 2025)
Labor pain during the active phase of the first stage is a major complaint that can cause anxiety and inhibit the progress of labor. Non-pharmacological interventions such as the use of a birthing ball are effective in reducing pain intensity. This study used a quasi-experimental design with a pre-test post-test with control group approach involving 30 laboring women (15 in the intervention group and 15 in the control group) at a Public Health Center in Maros Regency. Pain intensity was measured using the Verbal Rating Scale (VRS) or Numeric Rating Scale (NRS) before and 30 minutes after the intervention. The results showed a significant decrease in pain intensity in the intervention group (p=0.001) compared to the control group (p=0.125). It can be concluded that the use of a birthing ball is effective in reducing labor pain intensity during the active phase of the first stage.